KAPABILITAS KEPALA SEKOLAH DALAM MENINGKATKAN DISIPLIN GURU (STUDI DESKRIPTIF KUALITATIF DI SMP IT NURUL KHALIFAH BIMA) - Suraya Suraya; Kasman Kasman (FKIP, Universitas Palangka Raya, 2022)
Capability is a measure of the Principal of SMP IT Nurul Khalifah Bima in an effort to improve teacher work discipline. The capabilities referred to are Leadership and Teacher work effectiveness, namely collaboration and improvement of teacher HR Management. This type of research in this research is descriptive research with a qualitative approach. The data study techniques in this research consisted of observation, interview, and documentation. The results showed, so as to improve teacher discipline in attendance, the principal also provides a good role model for teachers by attending school on time, then optimizing the discipline rules for attendance. In addition, the Principal also seeks to collaborate with teachers by appointing teachers who declare them competent to supervise. The school principal also coordinates with the staff, which consists of 2 officers every day, namely from teachers who do not have teaching hours on that day and one person from the administration. The picket officer will circulate the class teacher attendance list that has been made so that they can see the teacher attendance level in each class. In addition, with an increase in teacher human resources, 70 percent of teaching staff with postgraduate education have produced quality resources, indicating the level of discipline.